5-4x=2x2+3

Simple and best practice solution for 5-4x=2x2+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-4x=2x2+3 equation:



5-4x=2x^2+3
We move all terms to the left:
5-4x-(2x^2+3)=0
We get rid of parentheses
-2x^2-4x-3+5=0
We add all the numbers together, and all the variables
-2x^2-4x+2=0
a = -2; b = -4; c = +2;
Δ = b2-4ac
Δ = -42-4·(-2)·2
Δ = 32
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{32}=\sqrt{16*2}=\sqrt{16}*\sqrt{2}=4\sqrt{2}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-4\sqrt{2}}{2*-2}=\frac{4-4\sqrt{2}}{-4} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+4\sqrt{2}}{2*-2}=\frac{4+4\sqrt{2}}{-4} $

See similar equations:

| 12+7q=14+16q | | 68=2s | | 41/2x=15 | | 5x+5=-8+3x+17 | | -11=6-2x-5 | | 5(w-6)-8=-7(-3w+6)-6w | | 27r=81 | | 4x-7+151=19x+9 | | +7x-14=+77 | | 3r+8=-12 | | 5/2d=10 | | 2/3x+3/2x+9=9/2x-4 | | 16-2r=+6r+1 | | 2=4.8g | | 66=6-5x | | 4x-12=4(3+x) | | 2÷3x-4=8 | | 7x-5(x+6=) | | –8g−–6g=–18 | | -4v-16=4(v-6) | | 5+x+2x+10=33 | | 3/5y+24=4-1/5y | | 6=3(w+6)-6 | | 1/8(4(x-1)+28)=x | | -3x-6=-6x-10+3x | | -8x+5(x+6)=6 | | –10y−–7y−–17=8 | | 3x+2=-9x+7 | | .75(x+12)=x+5 | | 9=x+49 | | 3x+9=7x´-5 | | 4-2(x-5)=x–19 |

Equations solver categories